Child's Personality and Family Upbringing Methods (Theoretical Study) - Mohammad AL-Momani; Elham Rababa (International Journal of Instructional Technology and Educational Studies)
The study aimed to identify the child's personality and family education methods in terms of the phenomenon of the child's attachment to the personality, the psychological security of the child in the personality, and the patterns of family upbringing in the personality; Where he used the descriptive and analytical approach to information, which is based on the principle of collecting information and interpreting it in a scientific way; The study found that the phenomenon of breastfeeding and attachment, the psychological safety of the child, and the patterns of socialization have a significant impact on the formation of the child's personality and making him able to communicate and interact with others correctly.Psychologists point out that there are critical and highly sensitive periods in the development of children during which learning of their behavior patterns becomes possible, that is, there are certain environmental interactions during this period in order to progress naturally, and at the beginning of his interaction he can issue a greater number of responses with his environment, but what remains From it and proves it is what keeps it consolidating, and what fades and omits from the responses, it is the one that does not support, and the child in the characteristics of his first life suffers from what befalls others and suffers from psychological disorders and emotional and behavioral deviations as adults suffer ( Watson,2019)